The influence of facilities and prices on consumer purchase intentions in the denai lama tourism village: a regression study - Siagian, Larasati Br; Lubis, Adelina; Pratama, Ikbar (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the influence of facilities and prices on consumer buying interest in the Denai Lama Tourism Village. Adequate facilities and affordable prices are two important factors that can increase the attractiveness of a tourist destination. The method used in this research is a regression study to identify the relationship between the independent variables (facilities and prices) and the dependent variable (consumer buying interest). The population in this study were tourists who visited the Denai Lama Tourism Village. The sample was taken using a purposive sampling technique, with a total of 98 respondents. Data was collected through a questionnaire that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression. The research results show that facilities and price have a significant influence on consumer buying interest. Meanwhile, price also has a positive effect, indicating that more affordable prices can increase consumer buying interest. The conclusion of this research is that improving the quality of facilities and setting competitive prices is an effective strategy to increase consumer buying interest in the Denai Lama Tourism Village. These findings provide practical implications for tourist destination managers in planning and developing appropriate facilities and pricing strategies to attract more visitors